Connecting energetics to dynamics in particle growth by oriented attachment using real-time observations - Lili Liu (Nature Portfolio, 2020)
Nanocrystal growth by oriented attachment remains poorly understood, despite being a prevalent pathway in geochemical, materials synthesis, and biomineral systems. Here, the authors show that zinc oxide nanocrystals grow by oriented attachment along the (001) plane driven by dipole-dipole interactions that align the particles at long distances prior to their collision and fusion.